Comparing Veterans with Posttraumatic Stress Disorder Related to Military Sexual Trauma or Other Trauma Types: Baseline Characteristics and Residential Cognitive Processing Therapy Outcomes. Issue 21 (November 2022) - Christ, Nicole M.; Blain, Rachel C.; Pukay-Martin, Nicole D.; Petri, Jessica M.; Chard, Kathleen M.
The Veterans Health Administration (VHA) has called for improved assessment and intervention for survivors of military sexual trauma (MST) to mitigate deleterious sequalae, including posttraumatic stress disorder (PTSD). Research on the impact of MST-related PTSD (MST-IT) on men is limited, and few studies have examined the differential effects of treatment across genders and MST-IT. Additionally, studies have utilized varying definitions of MST (e.g., sexual assault only vs. including sexual harassment), contributing to disparate outcomes across studies. Utilizing data from 343 veterans seeking residential cognitive processing therapy (CPT) for PTSD in VHA, this study examined the impact of MST-IT and gender on differences in demographic characteristics; pre-treatment severity of PTSD (overall and clusters), depression, and negative posttraumatic cognitions (NPCs); and post-treatment severity of these variables after accounting for pre-treatment severity. Results from 2x2 factorial ANOVAs found no differences in pre-treatment depression or overall PTSD by MST-IT, gender, or their interaction; however, MST-IT survivors presented with greater pre-treatment avoidance, global NPCs, and self-blame. Results from hierarchical linear regression models found only pre-treatment symptom severity significantly predicted post-treatment severity for overall PTSD and all NPCs. These findings suggest veteran survivors of MST-IT appear to benefit similarly from CPT delivered in a VHA residential PTSD program compared to veterans with other index traumas, regardless of gender. Although there were minimal post-treatment differences in PTSD and NPCs by MST-IT status and gender, residual symptoms related to negative cognitions and mood appear to differ across gender and MST-IT status. Specifically, in individuals without MST-IT, post-treatment PTSD symptoms of negative alterations in cognition and mood were higher in men than women. Moreover, women with MST-IT reported more symptoms of depression than both men with MST-IT and women without MST-IT. These findings suggest depressive symptoms decrease through residential PTSD treatment differentially by MST-IT status and gender and warrant further examination.